Low defect and high electrical conductivity of graphene through plasma graphene healing treatment monitored with in situ optical emission spectroscopy - Salehi, Mohammad; Bastani, Parnia; Jamilpanah, Loghman; Madani, Abbas; Mohseni, Seyed Majid; Shokri, Babak (Scientific reports, 2021)
Fundamental studies on graphene (Gr) and its real device applications have been affected by unavoidable defects and impurities which are usually present in synthesized Gr. Therefore, post treatment methods on Gr have been an important subject of research followed by the community. Here, we demonstrate a post-treatment of cm-sized CVD-grown graphene in a Radio Frequency-generated low-pressure plasma of methane and hydrogen to remove oxygen functional groups and heal the structural defects. The optimum plasma treatment parameters, such as pressure, plasma power, and the ratio of the gases, are optimized using in-situ optical emission spectroscopy. This way we present an optimal healing condition monitored with in situ OES. A twofold increase in the conductivity of plasma-treated Gr samples was obtained. Plasma treatment conditions give insights into the possible underlying mechanisms, and the method presents an effective way to obtain improved Gr quality.